The existential Joss Whedon evil and human freedom in Buffy the Vvampire Slayer, Angel, Firefly and Serenity - Richardson, J. Michael 1951-; Rabb, J. Douglas 1942- (McFarland & Company, Inc., 2007)
"Chapters cover such topics as Russian existentialism and vampire slayage; moral choices; ethics; faith and bad faith; constructing reality through existential choice; some limitations of science and technology; love and self-sacrifice; love, witchcraft, and vengeance; soul mates and moral responsibility; love and moral choice; forms of freedom; and Whedon as moral philosopher"--Provided by publisher